Virtual endocast of late Paleocene Niptomomys (Microsyopidae, Euarchonta) and early primate brain evolution. Issue 175 (February 2023) - White, Chelsea L.; Bloch, Jonathan I.; Morse, Paul E.; Silcox, Mary T.
Abstract: Paleogene microsyopid plesiadapiforms are among the oldest euarchontans known from relatively complete crania. While cranial endocasts are known for larger-bodied Eocene microsyopine microsyopids, this study documents the first virtual endocast for the more diminutive uintasoricine microsyopids, derived from a specimen of Niptomomys cf. Niptomomys doreenae (USNM 530198) from the late Paleocene of Wyoming. Size estimates of smaller-bodied uintasoricines are similar to those inferred for the common ancestor of Primates, so the virtual endocast of Niptomomys may provide a useful model to study early primate brain evolution. Due to the broken and telescoped nature of the neurocranium of USNM 530198, a μCT scan of the specimen was used to create a 3D model of multiple bone fragments that were then independently isolated, repositioned, and merged to form a cranial reconstruction from which a virtual endocast was extracted. The virtual endocast of Niptomomys has visible caudal colliculi, suggesting less caudal expansion of the cerebrum compared to that of euprimates, but similar to that of several other plesiadapiforms. The part of the endocast representing the olfactory bulbs is larger relative to overall endocast volume in Niptomomys (8.61%) than that of other known plesiadapiforms (∼5%) or euprimates (<3.5%). The petrosal lobules (associated with visual stabilization) are relatively large for a Paleocene placental mammal (1.66%). The encephalization quotient of Niptomomys is relatively high (range = 0.35–0.85) compared to that of Microsyops (range = 0.32–0.52), with the upper estimates in the range of values calculated for early euprimates. However, this contrast likely relates in part to the small size of the taxon, and is not associated with evidence of neocortical expansion. These findings are consistent with a model of shifting emphasis in primate evolution toward functions of the cerebrum and away from olfaction with the origin of euprimates.